The Conceptual Framework for Disabling Payment in International Trade Under the Jordanian Legal System - Emad Mohammad Al Amaren; Sultan Ibrahim Aletein (Fakultas Hukum Universitas Hang Tuah, 2022)
The past few years have witnessed a widespread movement of goods between parties in different states by utilizing letters of credit. Letter of credit has continued to play a massive role in expanding international trade since it is considered the most secure and stable banking service through which banks can finance foreign trade operations such as import and export. Although a letter of credit is regarded as a guarantee for the buyer and seller according to the Uniform Custom and Practice (UCP 600). Still, if the parties have to face some circumstances, they can withhold their obligation or even breach the L/C contract. This study aims to identify the reason behind stopping the payment for the beneficiary in the L/C. Through a qualitative and doctrinal legal approach, this study analyses the organization of UCP 600 regarding the compliance standards and the fraud exception. It also examines, via interviews with Jordanian bankers, academicians, and judges, the perceptions of the exception for stopping the payment in L/C transactions. The findings reveal that the Jordanian judiciary does not take avoidance and nullity of the underlying contract, conscionability, recklessness, contractual restrictions, and illegality as exceptions to the independence principle in the letter of credit.